Persistent primary hyperparathyroidism caused by an ectopic adenoma in the piriform sinus: case report and review of the literature - Sardella, Chiara; Seccia, Veronica; Giambalvo, Massimo; Pierotti, Laura; Dinoi, Elisa; Della Valentina, Simone; Pardi, Elena; Materazzi, Gabriele; Dallan, Iacopo; Berrettini, Stefano; Cetani, Filomena (Frontiers in Oncology, 2024)
Introduction: Primary hyperparathyroidism (PHPT) is a common endocrine disorder in which surgery is the only curative therapy. Ectopic parathyroid adenoma in the pyriform sinus resulting from a pathological migration of parathyroid glands along the embryological development is a rare cause of PHPT. We describe a case of a persistent primary hyperparathyroidism after previous unsuccessful surgery due to an ectopic parathyroid adenoma within the pyriform sinus and we review the previous reports on this issue. Case presentation: A 62-year-old woman was referred for persistent hypercalcemia following unsuccessful cervical exploratory surgery. Cervical ultrasound did not detect any parathyroid abnormalities. At variance, 99mTc-sestamibi SPECT/CT and CT scan of the neck identified a parathyroid adenoma in the left pyriform sinus, which was confirmed by endoscopy. The patient was successfully treated by transoral robotic resection and the pathology confirmed a parathyroid adenoma. Conclusions: The ectopic parathyroid adenoma in the pyriform sinus is so uncommon that only fourteen cases have been reported. However, the pyriform sinus should be considered a possible location of ectopic parathyroid glands, especially in the setting of persistent or recurrent PHPT after parathyroid surgery.